Passive smoking and its impact on employers and employees in Hong Kong - McGhee, S (BMJ Group, 2002)
Aims: To estimate the prevalence of passive smoking at work in the whole workforce in Hong Kong (population 6.8 million), the characteristics of the passive smokers, any extra use of health care among passive smokers, and who pays for that health care. Methods: A random sample of 14 325 households was contacted by telephone; 6186 responding adults who worked full time were asked about their employment, their most recent use of health care and the cost of that care, their medical benefits, and their exposure to secondhand smoke in the workplace. After weighting the sample for sex, age, household size, and income, 4739 subjects were included in the analysis. Results: Of 1961 full time workers who did not smoke, 47.5% were exposed to secondhand smoke in the workplace compared with only 26% exposed at home. Exposure at work was associated with being younger, male, married, less educated, and having a lower income. Those exposed at work were 37% more likely to report having visited a doctor for a respiratory illness in the previous 14 days. Employers were paying 28% of the cost of these visits, the government paid 8%, and the individuals paid 63%. If extrapolated to the 3 million workers in the Hong Kong population, employers would pay just over US$9 million per year, while the affected workers would pay around US$20 million. Conclusion: As well as the costs of active smoking, the cost of extra health care utilisation associated with passive smoking is an additional cost being paid by those employers who have not established smoke free workplaces and by their employees.